Effect of fiber source and particle size on chick performance and nutrient utilization. (8th August 2019) - Donadelli, R A; Stone, D A; Aldrich, C G; Beyer, R S
ABSTRACT: The addition of fiber in chick feeds is known to dilute nutrients; as a result, this may reduce nutrient digestibility and performance. However, recent studies suggest that moderate inclusion of insoluble fibers (2 to 3%) may stimulate gizzard development, which could result in better nutrient utilization and chick growth. The previous fiber sources evaluated were subject to wide fluctuation in their nutritional and chemical composition due to variation in processing. Miscanthus giganteus is a C4 grass purposefully grown for its fiber content which has a consistent fiber composition compared to food process residues. The objectives of this study were to determine the effect of dietary fiber source and particle size on day-old chick performance and nutrient digestibility. Day-old chicks (8 chicks per cage, 5 cages per treatment) were fed diets containing 3% of either sepiolite (SEP ), cellulose (CEL ), coarse beet pulp (BP ), fine BP, coarse Miscanthus grass (MG ), and fine MG. At the end of days 7, 14, and 21, chicks and experimental diets were weighed to compute average daily gain and feed intake. In addition, excreta from the previous 48 h of each data capture point was collected to determine nutrient digestibility. In general, chicks fed diets containing fiber consumed more feed, gained more weight, and had better feed conversion rate than birds fed the SEP diet. Particle size of the fiber had no effect on chick performance; however, nutrient utilization was higher ( P < 0.05) for chicks fed coarse fiber particles compared to these fed fine fiber particles. Birds fed diets containing MG performed similar to chicks fed CEL ( P > 0.05), but digestibility coefficients of birds fed BP diets were generally higher than chicks fed MG diets. In conclusion, chicks performed better with fiber in their diet and MG was comparable to CEL.